Multi-purpose fatigue sensor. Part 2. Physical backgrounds for damages accumulation and parameters of their assessment - M.V. Karuskevich; S.R. Ignatovich; T.P. Maslak; A. Menou; P.?. Maruschak; S.V. Panin; F. Berto (Fracture and Structural Integrity)
The characteristic informative parameters for defect detection to be used in fatigue sensors have been established. Their development is interpreted in terms of scale levels of deformation and fracture. Damage accumulation of the sensor’s surface tends to exhibit the self-organization nature. It is accompanied by formation of "folded" strain-induced relief on the surface. The mechanisms of damage accumulation under cyclic deformation were analyzed with the use of the multiscale approach. KEYWORDS. Defects; Fatigue sensors; Damage; Aviation.